Multi-criteria choice of alternatives based on hierarchy analysis method - Mikhno, Oleksii; Levinskova, Natalia (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
Background. When conducting descriptions of territories of a neighboring unfriendly state, as a rule, valid information about the development of such territories is hidden. Therefore, it is necessary to use the prognostic apparatus of expert evaluations based on information obtained from open sources. The article examines the basis of the military-geographical analysis of urbanized territories from the point of view of the application of expert assessments for many criteria. With a large number of options for prognostic decision-making, the question of choosing an alternative (decision option) should be fully justified. For such cases, it is advisable to use ranking based on the method of analysis of hierarchical structures. The purpose of such a description is to increase the validity of the decisions made during the selection of the optimal alternative by creating instrumental means of formalized evaluation of experts’ judgments. Methods. The following methods were used: system analysis in the formation of the urban environment metabolism model; the method of analyzing hierarchies when applying multi-criteria selection of alternatives; the method of expert evaluations as a global method of the condition determining of the object according to many criteria; methods of theory of sets and theory of utility, with the help of functions of which the advantages of making the appropriate decision on a set of acceptable alternatives were modeled. Results. From the proposed alternatives, based on the obtained utility functions, the most optimal alternative, in the opinion of experts, was chosen, which can be used during the planning of measures to ensure the sustainable development of the urban environment. The calculated characteristics of utility functions are used as criteria for choosing the optimal alternative. The proposed criteria and alternatives are presented in the form of a hierarchy. Conclusions. The article lays the groundwork for additional research and application of the methodology of analysis of hierarchies and the theory of utility in achieving the goals of sustainable development of urban areas in prognostic models of military-geographical analysis.